Validity and reliability of a Hausa language questionnaire assessing information, motivation and Behavioural skills for malaria prevention during pregnancy - Ahmed Dahiru Balami; Salmiah Md. Said; Nor'afiah Mohd Zulkefli; Norsa'adah Bachok; Bala Muhammad Audu (BMC, 2020)
Abstract Background Many studies on malaria knowledge, attitude and practice among pregnant women have been conducted in Hausa speaking communities in Nigeria. Despite this, no standard and uniform instrument for assessing this important public health problem has been developed in the Hausa language, even though it is widely spoken. The aim of this study was to develop and validate a questionnaire in Hausa language assessing information, motivation, and behavioural skills for malaria prevention during pregnancy. Methods The questionnaire was first developed in English language, and then assessed for its contents by a team of experts. It was then forwardly translated to Hausa, and backwardly translated again to English by independent language experts. These two English versions were then compared by a Public Health expert, following which the questionnaire was administered to 190 Hausa speaking antenatal care attendees. Exploratory factor analysis was performed on the data collected. Sixty three out of the 190 respondents were invited after 2 weeks to answer the same questionnaire, following which reliability tests were performed. Results The questionnaire showed good internal consistency, with Cronbach's alpha values of 0.859, 0.890 and 0.773 for information, motivation and behavioural skills constructs respectively. The motivation and behavioural skills constructs were able to delineate their items into three and two sub-sections respectively. The factor loadings for the two constructs ranged from 0.610 to 0.965. As for test retest reliability, the Krippendorff's alpha values for the items of the motivation section ranged from 0.941 to 0.996; that for behavioural skills ranged from 0.810 to 0.953, while for frequency of ITN use, it was 0.988. The Cohen's kappa values for the information section ranged from 0.689-0.974, except the item for 'fever' (zazzabi) which was 0.382, and was as such reworded to a simpler terminology 'hotness of the body' (zafin jiki). Conclusions The Hausa language IMB questionnaire on malaria in pregnancy demonstrated good validity, and a high level of reliability. It is as such recommended for use among Hausa speaking communities to ensure uniformity and objectivity.